Gadolinium alginate nanogels for theranostic applications - Podgórna, K; Szczepanowicz, K; Piotrowski, M; Gajdošová, M; Štěpánek, F; Warszyński, P (Colloids and surfaces. B, Biointerfaces, 2017)
Synthesis of theranostic nanoparticles, which combine both therapeutic and diagnostic capabilities in one platform can be considered as a step forward personalized medicine, since it allows tracing the delivery of the drug to targeted organ. Thus, the aim of this work was to prepare gadolinium alginate gel nanoparticles (gadolinum nanogels - GdNG) by the reverse microemulsions and physical crosslinking method as the vehicles able to carry hydrophilic drugs and to be traced by the Magnetic Resonance Imaging (MRI). The average size of synthesized nanoparticles was about 110nm and the batch concentration was 1010 particles/ml. The morphology of nanogeles was visualized by Cryo-Scanning Electron Microscopy. Surface of nanogels particles was modified by the Layer-by-Layer (LbL) technique using natural polyelectrolytes. The cytotoxicity of non-modified and LbL modified nanogels was evaluated by the cellular viability quantification and cell death assessments using MTT and LDH biochemical tests, respectively. We encapsulated the model compound - fluorescent dye (Rhodamine b) in nanogels networks and proved the possibility of GdNG visualization by MRI.
Keywords: algináty; polyethylenimin; Magnetic Resonance Imaging; Fluorescent Dyes; teranostická nanomedicína; Nanogels; Cell Line, Tumor; Polyethylene Glycols; Polyethyleneimine; LbL; lidé; Alginate; Theranostic; magnetická rezonanční tomografie; fluorescenční barviva; buněčná smrt; polyethylenglykoly; Alginates; Theranostic Nanomedicine; Cell Death; gadolinium; nanogely; Cell Survival; viabilita buněk; Polysaccharides; nádorové buněčné linie; Gadolinium; Humans